Pintamaan geokemiaa selittävät tekijät muuttuvassa tundraympäristössä - Virkkala, Anna-Maria (Helsingfors universitet, 2016)
Ongoing climate change is altering sensitive tundra environments. However, the impacts of these changes on topsoil geochemistry are still not fully understood even though their feedbacks might have the potential to change even the global climate system. Therefore, it is of great importance to study the relative importance of climatic and other environmental factors affecting topsoil geochemistry. This thesis examines the factors and processes regulating topsoil geochemistry and its sensitivity to climate change. The aim of the research was also to link local observations to regional models and predictions in order to improve the quality of digital soil maps. Field data (n=429) was collected from a landscape-scale research area (72 km²) in northern Norway (69° 90' N and 26° 20' E). Soil samples were analyzed in the laboratory and the concentrations of total nitrogen, phosphorous, total carbon, calcium, iron and pH were measured. Geochemical variables were modelled against environmental data comprising of soil moisture and derivatives of a climate model, an elevation model, Landsat-satellite images and aerial images. The relationships between the geochemical and environmental data were described using NMDS ordination method and modelled, predicted and simulated with generalized boosted models (GBM) and structural equation modelling (SEM). The distribution of the topsoil geochemistry based on the GBM model predictions was similar between the geochemical variables: there was a decrease of nutrient concentrations with increasing elevation and distance to tundra streams and with increasing mountain birch abundance. Topsoil geochemistry varied markedly over short distances, especially in mountain birch forest where the extreme ends of the geochemical gradient could be found even within a 100 m radius. Climate was the most important factor governing all the geochemical variables based on the GBM models but it affected topsoil geochemistry partly through soil moisture, the role of which was at times bigger than the role ...